TikTok Consumption Patterns for Shaping Student Values and Lifestyle at Brawijaya University - Bintang Corvi Diphda; Gertha Maria Gultom; Theofani Trudy; Talitha Salsabila Putri G; Puan Najwa Saras Vathi (Jurnal Studi Ilmu Sosial dan Politik, 2026)
Purpose: This research undertakes an analysis of the digital consumerism associated with the TikTok application among students at Brawijaya University. Its primary goal is to map and categorize the consumption patterns into two dimensions: Passive versus Active use, and Style versus Lifestyle motivation. Methodology: The study utilized a quantitative survey method to analyze digital consumerism among active students from 17 faculties at Brawijaya University. Data collection involved using a Google Form featuring a Likert scale instrument. The analysis employed a scoring and descriptive approach to interpret the total aggregate scores for the consumption categories. Results: The primary findings show that although passive consumption exists, the dominant pattern is active, largely defined by curation activities such as saving videos and using the search function for specific interests. Importantly, user motivation is predominantly Lifestyle-driven, meaning TikTok is integrated into personal values and routines, rather than being motivated purely by fleeting social trends or Style. Conclusions: Based from the findings, it can be concluded that TikTok is a significant and integrated part of their daily lives that reflects deeper personal interests and values rather than temporary trends. Limitations: The limitation of the study may not be broadly representative as the sample was limited to students from a single institution and relied solely on self-reported data. Contributions: This study offers a key contribution to Consumer Behavior by providing empirical evidence on the dominant active curation and Lifestyle-driven TikTok patterns among students, which can inform digital literacy efforts and marketing strategy development.